Collaborative Professional Development for Identifying English Learning Potential in Elementary Students with Intellectual Disabilities - Lum Pan Hpaulu (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This systematic narrative review investigates the impact of collaborative professional development (CPD) models—including co-teaching and inclusive instruction—on the capacity of elementary educators to identify and nurture English language learning potential in students with intellectual disabilities (ID). Drawing on a comprehensive synthesis of peer-reviewed empirical studies, theoretical frameworks, and case studies published between 2006 and 2025, the review reveals that effective CPD significantly shifts teacher perceptions from deficit-based to potential-oriented mindsets, thereby enhancing teacher self-efficacy and the implementation of inclusive pedagogical practices. Key findings demonstrate that interdisciplinary collaboration—particularly through Child Study Teams (CSTs)—supports teachers in differentiating between genuine language acquisition challenges and intellectual learning disabilities, thereby enabling more accurate educational placements. Despite these documented benefits, persistent systemic barriers hinder CPD implementation, including inadequate planning time, budgetary constraints, and inconsistent administrative support. This review concludes that cultivating a culture of shared professional responsibility, supported by structured, job-embedded development programs, is essential for establishing equitable learning environments in which students with ID can achieve their full educational potential.